Characteristics and Outcomes of Severe ARDS Patients Receiving ECMO in Southern Thailand. Issue 13 (October 2019) - Assanangkornchai, Nawaporn; Vichitkunakorn, Polathep; Bhurayanontachai, Rungsun
Extracorporeal membrane oxygenation (ECMO) is a treatment option considered for acute respiratory distress syndrome (ARDS) patients who are refractory to conventional treatments. However, treatment with ECMO has not shown significant reduction of mortality which may be due to inappropriate selection criteria. Thus, we aim to evaluate the treatment outcomes of patients treated with ECMO in our center and determine an optimal cutoff level of the Respiratory ECMO Survival Prediction (RESP) score for case selection. This was a retrospective case-control study conducted at Songklanagarind Hospital, Thailand, from January 2014 to August 2018. ECMO patients were randomly matched to a control group of patients with severe ARDS within the same time period. There were 19 cases diagnosed with ARDS and treated with ECMO and 57 controls with ARDS. The patients in both groups had an average APACHE II score of 30.2 (SD = 4.7) and mainly had bacterial pneumonia. The in-hospital mortality was not significantly different between the cases and controls (68.4% vs 63.2%, respectively); however, the ECMO cases had a significantly longer length of intensive care unit stay and cost of hospitalization. Active malignancy, male gender, PaO2 /FiO2 ratio, and hypotension needing vasopressors were the risk factors for mortality. The RESP score did not discriminate between the survivors and nonsurvivors. Thus, more patient is needed to construct a better selection criterion.